The Immunomodulator Effects of Biosynthetic Nanosilver Based on Immunoglobulin G Level of Mice Induced by Measles Vaccine Compared with Immunostimulant Agent - Dian Eka Ermawati; Putri Indah Nuraini; Niki Putri Anjani (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2024)
Inulin is a carbohydrate class contained in gembili tuber (Dioscorea esculenta (Lour.) Burkill) as a source of prebiotics to maintain immunity. Inulin can be used as a nanosilver bioreductor and increase the solubility of gembili's inulin. This study aims to determine the effectiveness of gembili's inulin nanosilver as an immunomodulator based on IgG levels of vaccine-induced Mice. Nanosilver at doses of 2 mg/KgBW, 4 mg/KgBW, 8 mg/KgBW, and 12 mg/KgBW was compared with synthetic immunostimulants to observe the type of immunomodulatory activity. This research was conducted in several stages, including the biosynthesis process, characterization, determination of nanosilver dose, animal conditioning, animal treatments, taking blood from retro-orbital sinuses, and ELISA reader. Blood serum obtained from the animals was analyzed for IgG levels using Mice IgG ELISA Kit and Spectrophotometer UV-VIS. The pH variation test was also conducted in this study which aims to determine the stability of the nanosilver solution at pH 8, 10, and 12. The results of the ELISA reader showed that the dose of 4 mg/KgBW. had the highest Optical Density value compared to other doses. Then, the comparison with synthetic immunostimulants produces p values of 0.13 0.05, which is not significantly different. Nanosilver inulin at 4 mg/KgBW. is the chosen dose as an immunomodulator with immunostimulant activity. The stability results showed that increasing pH changes do not affect the pH change of gembili's inulin nanosilver solution. It is because nanosilver's pH control and adjustment are still in the alkaline range.